Application of Regional Culture in Wooden Furniture Styling Design Based on Extension Semantics and Shape Grammar: Taking Su-Style Stool as an Example - Guanlan Xue; Jinglian Chen (BioResources)
In view of the current problems of insufficient furniture innovation and uniform styling, this article introduces regional culture to conduct innovative strategic research on existing wooden furniture styling, trying to explore the connection between furniture and culture. Based on the methods of extension semantics and shape grammar, the traditional Chinese furniture Su-style stool is used as an example to demonstrate its feasibility. This work mainly applies extension semantics to illustrate regional culture and combines shape grammar to integrate the cultural elements and furniture shapes, thereby creating new wooden furniture forms with regional cultural characteristics. The article not only draws a genealogy chart of Suzhou's regional culture, but it also extracts a number of semantics and graphics to describe Suzhou cultural characteristics. It expands the graphics into relevant elements as a replacement library to replace some of the DNA genes of the stool by shape grammar, allowing the new stool to carry the cultural memories of Suzhou. Finally, the work generated three design practices, which were evaluated by excellence evaluation method. In conclusion, the article demonstrated that the combination of extension semantics and shape grammar can effectively guide the design of wooden furniture with regional cultural characteristics.